2021
DOI: 10.1002/mnfr.202001099
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correlates and Impact of Dietary Lactoferrin Intervention and its Concentration‐dependence on Neurodevelopment and Cognition in Neonatal Piglets

Abstract: Scope: Lactoferrin (Lf ), a sialylated milk glycoprotein, promotes early neurodevelopment and cognition. Functional concentrations of Lf, however, remain unknown. Our objective is to determine the concentration-dependency of Lf on genes associated with neurodevelopment and cognition in neonatal piglets. Methods and results: Piglets are given milk replacer with Lf at concentrations of 155 (low) or 285 mg kg -1 day -1 (high) from postnatal days 3 to 38. Gene expression associated with neurodevelopment, cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…In agreement, Chen and colleagues showed that Lf modulates genes in a dose-dependent manner during early development of piglets in the absence of injury. Chen et al showed that, when administered at low doses (i.e., 15 mg/kg/day), Lf modulated genes (associated) related to brain development, whereas higher doses (2 g/kg) should be used for neuroprotection [50]. Interestingly, our study shows that despite the molecular neuroprotection using the highest dose of Lf (10 g/kg), tissue damage was not reversed.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In agreement, Chen and colleagues showed that Lf modulates genes in a dose-dependent manner during early development of piglets in the absence of injury. Chen et al showed that, when administered at low doses (i.e., 15 mg/kg/day), Lf modulated genes (associated) related to brain development, whereas higher doses (2 g/kg) should be used for neuroprotection [50]. Interestingly, our study shows that despite the molecular neuroprotection using the highest dose of Lf (10 g/kg), tissue damage was not reversed.…”
Section: Discussioncontrasting
confidence: 51%
“…The neuroprotective effects of Lactoferrin have been attracting widespread attention among clinical and preclinical researchers in the last years [50,83]. Kaufman and colleagues administered up to 300 mg/day of enteral bovine Lf and reported no adverse effects in preterm babies [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increase in the BDNF-polySia complex levels in the brain might be considered to be the main mechanism by which Lf affects neurodevelopment and cognitive formation [ 45 ]. In fact, an extended study by Chen et al provided new evidence supporting the regulation of BDNF signaling by exogenous Lf intervention and elucidated the molecular mechanisms underlying the concentration-dependent effect of Lf supplementation on promoting neurodevelopment and cognition in neonatal piglets [ 148 ].…”
Section: Lf In Developmental Delay In Childrenmentioning
confidence: 99%
“…Moreover, BDNF, which is mainly released by astrocytes, is known to contribute to several aspects of neuronal development and function, such as synaptic plasticity, neuronal survival and differentiation, neuronal process growth, and neuronal repair following injury [ 178 ]. Interestingly, BDNF expression is up-regulated after Lf treatment [ 45 , 64 , 88 , 89 , 148 , 153 ], suggesting that some functions of astrocytes may be activated.…”
Section: Perspectives and Challengesmentioning
confidence: 99%